2007
DOI: 10.1016/j.jinf.2006.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid treatment of severe acute respiratory syndrome in Hong Kong

Abstract: We speculate that corticosteroid with higher in-vitro inflammatory potency administered at timing and dosages commensurate with disease severity may be conducive to better outcome from SARS as a consequence of more effective control of immunopathological lung damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…Several other cohort studies report that steroid use was associated with detrimental outcome ( Auyeung et al., 2005 ; Leung et al., 2005 ; Ng et al., 2004 ; Wang et al., 2005 ; Xie et al., 2005 ; Yam et al., 2007 ). Two retrospective cohort studies report that steroid use was associated with a higher risk of ICU admission and mortality ( Auyeung et al., 2005 ; Yam et al., 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several other cohort studies report that steroid use was associated with detrimental outcome ( Auyeung et al., 2005 ; Leung et al., 2005 ; Ng et al., 2004 ; Wang et al., 2005 ; Xie et al., 2005 ; Yam et al., 2007 ). Two retrospective cohort studies report that steroid use was associated with a higher risk of ICU admission and mortality ( Auyeung et al., 2005 ; Yam et al., 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since COVID-19 was first reported in December 2019, it has attracted global attention owing to its similarity to SARS-CoV and MERS-CoV in causing fatal respiratory disease, and its potential for causing large-scale human infection and economic disruption. When considering patients with SARS and MERS, the use of corticosteroids therapy is still debated (20,21). Corticosteroids therapy was used in the treatment of severe SARS because early anecdotal experience supported it, and radiological findings, and histologic features of critically ill patients with SARS were similar to those of patients with ARDS (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…[16] Available data on systemic glucocorticoid therapy among coronavirus-infected patients mainly comes from studies of patients with SARS and MERS, but whether glucocorticoid therapy is definitively beneficial in the clinical management of these two coronavirus infections is still being debated. [13,20,21] Glucocorticoid therapy was used in the treatment of severe SARS because early anecdotal experience supported it, and radiologic findings and histologic features of critically ill patients with SARS were similar to those of patients with acute respiratory distress syndrome (ARDS). [22][23][24][25] As early as March 2003, China first summarized its experience in the management of SARS, and suggested that high-dose glucocorticoids should be used if patients had fever persisting for more than 3 days, or radiologic findings were suggestive of persistent lung involvement or progressive deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…[53] It has been noted that if lung injury has been effectively controlled, appropriate doses of glucocorticoids based on disease severity may be beneficial for better outcomes of SARS. [10,21] In our study, we will investigate whether the use of mid-dose and shortcourse adjunctive glucocorticoid therapy to treat severe COVID-19 is advantageous, safe, and effective.…”
Section: Discussionmentioning
confidence: 99%